Enabling sesame farmers through the provision of market information and collective action - Kassie, Girma T.; Asnake, Woinishet; Worku, Yonas; Abate, Gashaw T.; Mesfin, Selamawit; Minot, Nicholas (CGIAR System Organization, 2025)
This study aims to assess the effect of market information (MI) and collective action (CA) on sesame production, marketing, and behavioral outcome variables in northwest Ethiopia. We conducted an individually randomized group-treatment trial in which 1560 farm households were randomly divided into three groups: control, market information only (MI), and market information and training in collective action (MICA). The baseline survey covered all 1560 households, while the endline survey covered 1,512 households. We estimated intention-to-treat, average treatment effect, and local average treatment effects for each group. The results showed that for those who actually received MI and MICA, satisfaction with access to market information increased by 22% and 21%, respectively. For those who received MI, satisfaction in being part of a collective marketing action increased by 11% and 22%, respectively, compared to those who did not receive MI or MICA. These results call for a recommendation on packaging market information and collective action efforts to enable farmers to make more informed production and marketing decisions. We also recommend implementing similar studies with a more reasonable duration to evaluate the effects of such interventions, which have enormous potential to improve the production and marketing efficiency of smallholder farmers.